Féminismes - Babin, Sylvette; Griffiths, Jennifer; Behiery, Valerie; Buurman, Nanne; St-Gelais, Thérèse; Dubois, Anne-Marie; Toulouse (Esse arts + avis, 2017)
Ce numéro s’intéresse aux rapports singuliers entre l’art et les féminismes. En tenant compte de la multiplicité des subjectivités et de l’hétérogénéité des femmes, il s’agit de faire connaitre comment les multiples pratiques et les théories sur l’art participent à déconstruire les oppressions et les limites liées au genre. On présente une sélection de pratiques féminines et féministes, militantes ou non, issues d’approches et de communautés diverses. Les différentes revendications, prises de position et affirmations témoignent de la diversité des artistes : subversion, soulèvement protestataire, remise en question des archétypes de genre et d’hétéronormativité, approche féministe postcoloniale, résurgence des pratiques ancestrales, représentation de soi, utilisation consciente et assumée de la séduction sont autant de manières de dire, encore, la nécessité des féminismes.
Publisher: Presses de l'Université du Québec à Montréal
Keywords: approches et analyses; art contemporain; artistes féministes; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; féminisme islamique; har4600; histoire de l'art; intersectionnalité; premier cycle; thématiques

Islamicate Sexualities: The Artworks of Ebrin Bagheri - Gayed, Andrew (esse arts + opinions, 2017)
As a push against colonial forces and imperialism, homosexuality in the Middle East was historically made into an illegal identity category—one that, many argue, did not exist prior to increased contact with Western explorers and travellers. It is important to understand how the emergence of the Gay International coincided with that of Western gay sexuality studies. These issues are all at the forefront in the study of Islamicate sexualities. “Islamicate,” as defined by Marshal Hodgson, refers not directly,to the religion of Islam itself, but to the social and cultural complexities historically associated with Islam, including non-Muslims living within the same regions. Only by keeping imperialism at the forefront of the study of sexualities can we better situate how pre-modern Islamicate sexual scripts have resisted complete colonization and continue to exist in the diaspora.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; asie; canada; cours; discipline; féminisme islamique; har4600; histoire de l'art; iran; premier cycle; queer; ressource en ligne; régions géographiques; thématiques

Veil: veiling, representation, and contemporary art - Tawadros, Gilane; Bailey, David A. (MIT Press ; IVA, 2003)
No single item of clothing has had greater influence on Western images of Middle Eastern and North African women than the veil. The fascination of Western writers, artists, and photographers with the veil reflects the voyeuristic nature of our interest in what is strange and "other." Veil, which accompanies an exhibition organized by the Institute of International Visual Arts in London, explores the representation of the veil in contemporary visual arts. Providing a context for the commissioned essays are a number of classical historical texts crossing religions, cultures, genders, and ages–from Greek myths to articles published in the aftermath of September 11, 2001. Some of the contemporary artists and scholars write autobiographically about the meaning of the veil in their lives. Others take a more political approach, discussing, for example, how the events of September 11 changed the use and reception of veil imagery throughout the world. Still others take a historical approach, examining how nineteenth-century technological developments in travel and photography led to photographic depictions of both the veiled and unveiled body in relation to landscape. A number of essays look at the art historical precedents for the current interest in artwork addressing the veil, while others examine how codes of modesty and gender segregation have affected the making and viewing of films in postrevolutionary Iran. The essays are by Jananne Al-Ani, David A. Bailey, Alison Donnell, Ghazel, Salah Hassan, Reina Lewis, Hamid Naficy, Zineb Sedira, and Gilane Tawadros. The artists represented include Faisal Abdu'Allah, Kourosh Adim, Ghada Amer, Jananne Al-Ani, Farah Bajull, Samta Benyahia, Gaëtan de Clérambault, Marc Garanger, Shadafarin Ghadirian, Group AES, Emily Jacir, Ramesh Kalkur, Shirin Neshat, Harold Offeh, Gillo Pontecorvo, Zineb Sedira, Mitra Tabrizian, and Elin Strand.
Section: 187 p. : illustrations en noir et en coul. ; 22 cm
Keywords: afrique; afrique du nord; approches et analyses; arts; corps; cours; discipline; féminisme islamique; har4610; histoire de l'art; mode; moyen-orient; point de vue situé; premier cycle; régions géographiques; thématiques; vêtements